Pelaksanaan Indikasi Geografis oleh Masyarakat Perlindungan Indikasi Geografis (Mpig) Pasca Sertifikasi di Kepulauan Meranti dan Solok - Rialin, Monarisya; Daulay, Zainul; Delfiyanti, Delfiyanti (UNES Law Review, 2023)
Geographical indications on a product can increase the economy if used and protected properly. However, not all registered Geographical Indication products experience significant price increases after certification, such as Sago Meranti. Therefore the role of the Geographical Indication Protection Society (GIPS) in post-certification governance is very important and influences the welfare of its members. This research is a normative-empirical research through a comparative approach using primary and secondary data. Based on the research, the results obtained were: 2. It is known that the implementation of Geographical Indications by the Sago Meranti Community Association (AMSM) has not been running optimally, marked by the not using the Geographical Indication logo on its product packaging which has not caused an increase in the price of Sago products, on the other hand, Geographical Indication Protection Society of Liberika Coffee Rangsang Meranti and Bareh Solok have experienced an increase in yield. production and price increases so as to have an impact on increasing the income of its members. 3. Alternative models used for Sago Meranti Community Association are a. Formation of legal policies by the Regional Government b. Management of quality and characteristics through the development of internal control guidelines, and 3. Marketing methods through the use of the Geographical Indication logo on product packaging and cooperation with the private sector and the Government.